The Lansdowne era : Victoria College, 1946-1963 - Harvey, Edward B., 1939- (Published for the University of Victoria by McGill-Queen's University Press, 2008)
Demographic, economic, and social change between 1946 and 1963 affected all of Canadian society and profoundly shaped what was then Victoria College.